PENGARUH BERBAGAI ZAT PENGATUR TUMBUH (ZPT) TERHADAP PERTUMBUHAN STEK BATANG PULAI RAWA (Alstonia spatulata) - Winda Ningsih Pardede; Gusti Muhammad Hatta; Damaris Payung (Jurnal Sylva Scienteae, 2021)
Some of the goals that exist in this research are to analyze how the effect of giving Rootone F, giving Rootmost and giving Bean Sprouts Extract to the growth response of stem cuttings in Pulai Rawa (Alstonia spatulata. Growth Regulatory Substances used in this study there are 3 types of treatments such as giving Rootone F as the first treatment, the second treatment is by giving rootmost and by giving Bean Sprouts Extract as the third treatment and in this study there is control as one of the comparison between the differences between Stem cuttings that use Growth Regulatory Substances with no provision of ZPT. In November 2019 until January 2020 this study took place in the shade house of the forestry faculty at Lambung Mangkurat University.  RAL (Completely Randomized Design) The method used in this study is to use with a set of 4 treatments that were repeated 20 times in each treatment, then there were 80 experimental units in this study.  The results obtained in this study showed the effect of various growth regulators which differed to the response of the growth of Pulai Rawa plant stem cuttings.  The provision of rootone F did not affect the growth response while the administration of Growth Regulator Substance Rootmost gave an effect on the response of root growth of Pulai Rawa cuttings (Alstonia spatulata) and by giving Bean Sprout Extract which had an influence on the growth in number of cuttings.Keywords : Growth regulators; Stem cuttings; Pulai Rawa